Effect of different dialysate temperatures on post dialysis fatigue in patients undergoing haemodialysis: a quasi-experimental study - Anwar, Aizaz; Arshad, Abdul Rehman; Sadiq, Muhammad Arif; Saleem, Muhammad Zulqarnain; Muhammad Iqbal; Abbas, Muttahar (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the effects of warm and cold dialysate solutions on the duration of post-dialysis fatigue in patients undergoing maintenance haemodialysis. Method: The quasi-experimental study was conducted at the Department of Nephrology, Pak Emirates Military Hospital, Rawalpindi, Pakistan, from May 9 to September 10, 2023, and comprised adult patients of either gender undergoing maintenance haemodialysis for a minimum 3 months. The patient initially underwent haemodialysis with a dialysate temperature of 36°C for 2 weeks. During the subsequent washout period of one week when the dialysate temperature was not monitored, they underwent haemodialysis with a dialysate temperature of 37°C for another 2 weeks. Blood pressure was monitored every 30 minutes to record any hypotensive episodes. Patients were asked if they felt fatigued after the last haemodialysis session, and the duration was noted down. Data was analysed using SPSS 24. Results: Of the 92 patients with mean age 49.1±16.1 years, 57(62%) were males. Post-dialysis fatigue was seen in 67(72.8%) and 75(81.5%) patients with dialysate temperatures at 36°C and 37°C, respectively (p<0.001). The duration of post-dialysis fatigue was also significantly longer at dialysate temperatures 37°C p<0.001). There was no significant difference in the proportion of hypotensive episodes in the two groups (p=0.445). Conclusion: Dialysate temperature 36°C was found to be associated with less frequent and shorter duration of post-dialysis fatigue compared to dialysate temperature 37°C. Key Words: Cold temperature, Fatigue, Haemodialysis, Haemodialysis solutions, Hypotension, Renal replacement therapy.